Modelo de simulación de apendicectomía abierta en la educación virtual para estudiantes de medicina durante la pandemia de COVID-19 - Cornejo-Carrasco, Consuelo E. (2023)
Objective: To evaluate the skills achieved by the undergraduate medical student in performing an open appendectomy and purse string in the simulation model created, to evaluate the degree of satisfaction of its use and to determine its costs. Method: Pre-experimental, prospective and longitudinal study. The skills achieved by 24 undergraduate medical students in performing an open appendectomy and purse string in the simulator were evaluated using the OSATS (Objective Structured Assessment of Technical Skills) through virtual teaching. A survey was conducted to the students to evaluate the simulator and its costs were determined. Results: There was a significant increase in the OSATS of the skills achieved, from 7 (pre-test) to 26 ± 5.71 points (final post-test) (p = 0.0001) and reduction in the operative time from 12 ± 3.81 minutes (first post-test) to 8 ± 2.02 minutes (final post-test) (p = 0.0001). 41% of the students were totally satisfied with the achievements obtained and 59% partially satisfied. The cost of the simulator was 4.64 USD. Conclusions: The students achieved an improvement in their skills in the surgical technique. This simulation model is low cost and presents an adequate level in the satisfaction of the achievements obtained by the students.